Efektivitas Penyuluhan Kesehatan Gigi dengan Metode Stratagem dan Metode Snowball Throwing dalam Meningkatkan Pengetahuan Karies Gigi pada Murid Kelas IV, V, dan VI SDN Dalam Pagar Ulu 2 Martapura Timur - Rahmatanti, Rinda Dwi; Said, Fahmi; isnawati, isnawati (Poltekkes Kemenkes Banjarmasin, 2023)
One of the promotive efforts to prevent dental caries is the need for early dental health education for elementary school-aged children. The results of the 2020 UKS/UKGS data by the East Martapura Public health center at SDN Dalam Pagar Ulu 2 showed that 67 out of 72 students were affected by caries. This study aims to determine the effectiveness of dental health counseling with the stratagem method and the snowball throwing method in increasing knowledge of dental caries in class IV, V, and VI SDN Dalam Pagar Ulu 2 Martapura Timur. The type of research is analytical research with a quasi experiment design and approach non randomized control group pretest posttest design. The research population was 36 people. The sampling technique used was total sampling using the Independent Sample T-Test to determine the effectiveness of increasing knowledge of dental caries after counseling between the two methods. The mean before and after counseling of the stratagem method, which was 15.17, increased to 19.11 with a difference of 3.94, while the mean before and after counseling of the snowball throwing method was 16.94, which increased to 19.78 with a difference of 2.84. The results of the Independent Sample T-Test showed that the p-value was smaller than alpha. The conclusion is that counseling using the stratagem method is more effective than counseling using the snowball throwing method on dental caries knowledge. It is recommended to choose the stratagem method in counseling because this method has proven to be more effective in conveying and receiving dental caries knowledge. Keyword : Statagem method, Snowball throwing method